THE FORECASTING OF THE RESIDUAL RESOURCE OF ELECTRONIC ENGINE CONTROL SYSTEM - Y. V. Bazhenov; V. P. Kalenov (Вестник СибАДИ)
In the article authors have given the results of research operating reliability of electronic engine control module systems (ECM), substantiated the set of diagnostic parameters for the estimation of the technical condition of the subsystems (ECM) and their standard value, built graphics and analytical equations describing the patterns of changes diagnostic parameters in the meantime. The method of forecasting of residual resource of structural elements ECM was given with the using of confidential interval. The method was tasted on the example of forecasting of the residual resource of the power subsystem fuel ECM 1.6 THP Turbo Tiptronic (110 кВт) the Peugeot 208.